MEMUPUK SIKAP SALING MENGHARGAI MELALUI PENYULUHAN ANTI BULLYING DI SDN GUNUNG SUMBUL KECAMATAN CIOMAS, KABUPATEN SERANG - Tabroni Tabroni; Rahmatullah Jundi; Ahmad Rieza Nurfaathir; Raihan Agustian; Mulyati Mulyati; Reviana Qori Rahayu (Indonesian Collaboration Journal of Community Services, 2023)
The purpose of this activity is to provide education regarding the urgency of stopping bullying behavior and developing a sense of empathy in social relations. The main focus is preventing acts of abuse against children and raising awareness of the importance of respecting one another. This service approach is carried out through counseling sessions which aim to provide insight into the importance of stopping bullying and cultivating an attitude of respect. Based on the feedback received from extension participants, especially students, this activity plays an important role in educating children about ways of interacting that support a positive environment. The results of this activity show an increased understanding of the importance of behaving positively in social interactions, and avoiding using degrading words, physically aggressive behavior, or ridiculing one's physical appearance, which can hurt other people's feelings. During the implementation of this activity, students showed great enthusiasm because they realized the important value of this guide in forming good relations in school and society. They begin to understand that language that contains ridicule or condescension, even in the form of jokes, is included in the category of bullying behavior. Therefore, this service activity has a key role in providing education about the ethics of interacting and respecting others. Therefore, it is hoped that this service activity can have a positive impact on students and can be implemented in a sustainable manner, especially in fostering mutual respect through the anti-bullying counseling program at Gunung Sumbul Elementary School, Ciomas District, Serang Regency